PSYCHOLOGICAL HEALTH OF A FUTURE TEACHER IN THE EDUCATIONAL SPACE OF A PEDAGOGICAL UNIVERSITY (Web of Teachers: Inderscience Research, 2023)
This article discusses the importance of the psychological health of a future teacher in the context of his training at a pedagogical university. The authors emphasize that psychological health plays a decisive role in the formation of a successful teaching career and quality education. The article examines the main aspects of psychological health, such as self-understanding, resilience, emotional intelligence, ethics, research and support from the teaching community. In addition, she discusses the importance of supporting future educators and developing special programs to develop psychological skills in educational institutions.